Understanding the Eastward Shift and Intensification of the ENSO Teleconnection Over South Pacific and Antarctica Under Greenhouse Warming - Wang, Ya; Huang, Gang; Hu, Kaiming; Tao, Weichen; Gong, Hainan; Yang, Kai; Tang, Haosu (Frontiers in Earth Science, 2022)
The Pacific-South America (PSA) teleconnection pattern triggered by the El Niño/Southern Oscillation (ENSO) is suggested moving eastward and intensifying under global warming. However, the underlying mechanism is not completely understood. Previous studies proposed that the movement of the PSA teleconnection pattern is attributable to the eastward shift of the tropical Pacific ENSO-driven rainfall anomalies in response to the projected El Niño-like sea surface temperature (SST) warming pattern. In this study, we find that with uniform warming, models will also simulate an eastward movement of the PSA teleconnection pattern, without the impact of the uneven SST warming pattern. Further investigation reveals that future changes in the climatology of the atmospheric circulation, particularly the movement of the exit region of the subtropical jet stream, can also contribute to the eastward shift of the PSA teleconnection pattern by modifying the conversion of mean kinetic energy to eddy kinetic energy.